Ketimpangan Hukum dalam Kasus Ferdy Sambo: Tijauan Keadilan dalam Prespektif Aspek Transendental “Unum, Verum, Bonum dan Pulchrum“ - Kuniberth De Forbin Janson Seran; F.X. Armada Riyanto; Mathias Jebaru Adon (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
"Indonesia is a state of law", reads the 1945 Constitution, article 1 paragraph 3. This means that all aspects of life in society and state affairs are governed by law. This research discusses the legal inequality in the Ferdy Sambo case and its relation to the transcendetal aspects of metaphysics; Unum, Verum, Bonum and Pulchrum. The purpose of this research is to clarify the injustice and manipulation of power carried out by Ferdy Sambo and to reveal the important influence of the values of Unum, Verum, Bonum and Pulchrum in an effort to emphasize legal identity and efforts to realize justice. The approach used in this research is literature analysis related to the topic of discussion and empirical normative studies. Based on the research results, it can be concluded that legal policies that should reflect justice and truth are often not in accordance with the reality in society. Law is often manipulated for personal interests, especially by individuals who have access and power in it. One of the efforts to restore the law is to instill legal awareness based on the values of Unum, Verum, Bonum and Pulchrum.